2021
DOI: 10.1016/j.intmar.2020.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Spot-On Creativity: Creativity Biases and Their Differential Effects on Consumer Responses in (Non-)Real-Time Marketing

Abstract: A challenge in digital content marketing is to create meaningful messages on meaningful moments. To do so, brands frequently align social media messages with topical moments, also known as Real-time Marketing (RTM). While RTM aims to make meaningful connections, the creative development is subject to time pressure due to its real-time nature, which could have a negative effect on originality and craftsmanship, two other creativity dimensions besides meaningfulness which drive consumer responses. We address thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 80 publications
0
40
1
1
Order By: Relevance
“…Specifically, the creative process often entails clarifying a problem and need (researching, analysing, and synthesizing), generating ideas (planning, ideation and divergent thinking), testing and experimentation (convergent thinking), and inference and finalization (idea engineering and actualizing a product; Kapkın & Joines, 2021). Criteria for evaluating the creativity of a product often include the product's novelty, usefulness (Chang et al, 2016), and elaboration or aesthetics (Besemer, 1998; Lan & Kaufman, 2013; Mazerant et al, 2021; Weisberg et al, 2021). These criteria were incorporated into the current study to test the following hypotheses.H2 VR application in teaching significantly affects the creative process.H3 VR application in teaching significantly affects creative design performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Specifically, the creative process often entails clarifying a problem and need (researching, analysing, and synthesizing), generating ideas (planning, ideation and divergent thinking), testing and experimentation (convergent thinking), and inference and finalization (idea engineering and actualizing a product; Kapkın & Joines, 2021). Criteria for evaluating the creativity of a product often include the product's novelty, usefulness (Chang et al, 2016), and elaboration or aesthetics (Besemer, 1998; Lan & Kaufman, 2013; Mazerant et al, 2021; Weisberg et al, 2021). These criteria were incorporated into the current study to test the following hypotheses.H2 VR application in teaching significantly affects the creative process.H3 VR application in teaching significantly affects creative design performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This will increase consumers' importance to the relationship and, in turn, lead them to be more motivated to participate in the account and eventually make purchases (Casaló et al, 2021). In response to being creative on Instagram, a study by Mazerant et al, (2021) implies that one particular brand message cannot be posted on all social media platforms, which means, when designing brand messages, the medium context and its functionalities should be taken into account.…”
Section: Theme 2: the Use Of Instagram To Market Products During The ...mentioning
confidence: 99%
“…It is also suggested that craftsmanship is the most critical driver of consumer responses. Primarily, on a visual-oriented platform such as Instagram, practitioners should focus on the visual attractiveness of brand messages (Mazerant et al, 2021).…”
Section: Theme 2: the Use Of Instagram To Market Products During The ...mentioning
confidence: 99%
“…To date, marketing is about constantly innovating to deliver successful strategies and provide new customer solutions (Grewal, Noble, Roggeveen, & Nordfält, 2020;Inman & Nikolova, 2017;Pantano, Priporas, & Stylos, 2018;Pantano & Vannucci, 2019). The ability of managing new and creative approaches and appraising the relative role and value in the marketing development would secure the company's profitability, resulting in the longevity of the company and its brands (Mazerant, Willemsen, Neijens, & van Noort, 2021;Meesuptong, Jhudra-Indra, & Raksong, 2014;Slater, Hult, & Olson, 2010). However, it goes beyond the development and marketing of new products.…”
Section: Prefacementioning
confidence: 99%